Communal and agentic teacher behavior in teacher-child dyads. A new self-report scale based on a circumplex approach - Kreutzmann, Madeleine; Frühauf, Madita; Hannover, Bettina; Koeppen, Karoline (Frontiers in Education, 2024)
IntroductionThe goal of this study was to develop a self-report scale measuring the teacher’s interpersonal behavior in teacher-child dyads in elementary schools and to provide evidence of the scale’s validity. Using the framework of interpersonal theory, the Questionnaire on Dyadic Interpersonal Teacher Behavior (DITeB) models teacher behavior in an interpersonal circumplex that allows for the simultaneous analysis of teacher behavior along the two orthogonal dimensions of communion (warmth) and agency (guidance, monitoring).MethodsWe analyzed 440 dyadic teacher-child relationships derived from 88 teacher reports. Teachers rated the 20 items (8 scales) of the DITeB to describe their interpersonal behavior towards a child. To test the scale’s structural validity, we conducted confirmatory circumplex structural analyses. To test the scale’s construct validity, we used teachers ‘descriptions of relationship quality (closeness, conflict, dependency), and of their child related emotions (enjoyment, anger, anxiety). In addition, teachers reported on the child’s academic performance (numeric grades), as well as their professional beliefs about heterogeneity and self-efficacy for adaptive teaching, data which were used for further construct validation.ResultsWe obtained empirical support for both structural and construct validity of the DITeB. Teacher interpersonal behavior correlated significantly with perceived relationship quality and emotions: high relationship quality and positive emotions were associated with high communion and low agency, whereas low relationship quality and negative emotions were associated with low communion and high agency, supporting construct validity. Additionally, as child’s academic performance improved, teachers’ agency decreased. Towards different groups of children, teachers’ interpersonal behaviors varied systematically based on their professional beliefs: teachers with strong heterogeneity beliefs tended to be more communal towards low-performing children compared to high-performing children. Moreover, teachers with strong self-efficacy towards adaptive teaching adjusted their agency more flexibly according to children’s performance in school, further supporting the construct validity of our instrument.DiscussionWe discuss how our instrument enriches the spectrum of existing scales on interpersonal teacher behavior. By focusing dyadic specific teacher behavior, the DITeB allows examining the extent to which the teacher adapts their behavior to child characteristics (adaptive teaching), and the effect of teacher behavior on child outcomes.